The successive parameterization method of control actions in boundary value optimal control problems for distributed parameter systems - Pleshivtseva, Yu. E.; Rapoport, E. Ya (Journal of computer & systems sciences international, 2009)
A special procedure for control action parameterization and the precise method based on it for determining open-loop optimal control algorithms for the systems with distributed parameters under the prescribed tolerance conditions for the deviation from the required final state of the controlled parameter being estimated in the uniform metric is proposed. The method uses the reduction to the problems of semi-infinite optimization, alternance properties of their solutions, and some additional information on fundamental regularities of the subject domain. Examples showing an opportunity of using these results for applied problems, constituting also a point of independent interest are presented.